Sunlight mediated passive wastewater treatment technology using photochemical reduction of ferric iron for decontamination of various aqueous contaminants. (October 2018) - Dominic, John Albino; Somathilake, Purnima; Achari, Gopal; Langford, Cooper H.; Tay, Joo-Hwa
Graphical abstract: Highlights: Demonstrates novel, passive, advanced oxidative process mediated by sunlight. Photochemical Fe(III) reduction under sunlight degrades carbamazepine and sulfolane. Complete degradation of carbamazepine in 2 h under sunlight. Demonstration of the process in actual treated effluent and groundwater. In 7 h, 60% reduction of acid extractable organics in oil sand process water. Abstract: This paper demonstrates the feasibility of a very simple and novel, "passive" sunlight mediated photochemical process using ferric chloride for degradation of a wide range of organic contaminants. Batch experiments were conducted under natural sunlight to study the degradation of carbamazepine (CBZ), sulfolane and acid extractable organics of oil sands process water (OSPW) in the presence of 100 mg/L of ferric chloride at pH 2.7–3. The efficacy of the process was also evaluated by studying the degradation of the contaminants in actual wastewater and groundwater samples. All three contaminants were resistant to photodegradation under sunlight in the absence of ferric chloride. CBZ in wastewater and pure water was completely degraded in the presence of ferric species under sunlight within 2 h. Kinetics of degradation of CBZ was fastest in groundwater as more than 99.9% of CBZ was degraded within 30 min. Rate of reduction of Fe(III) to Fe(II) was proportional to kinetics of CBZ degradation in aqueous samples. Over an irradiation period of 7 h, more than 50% of TOC was removed by sunlight mediated iron reduction of CBZ in spiked water and secondary treated wastewater. In contrast to CBZ, sulfolane degraded faster in deionised water (4.5 h −1 ) with more than 50% reduction in TOC. Unaltered rates of increase in Fe(II) concentration in groundwater spiked with sulfolane and CBZ signifies the presence of easily degradable organics in groundwater competing with sulfolane for the reactive species. GC–MS analysis showed more than 60% reduction in acid extractable organics present in OSPW 7 h of sunlight irradiation in the presence of ferric chloride. Overall, photochemical iron reduction shows great promise as highly sustainable treatment process for decontamination of variety of recalcitrant contaminants in their inherent aquatic environments with marginal effects imparted by other aquatic species.